Associations between blood sex steroid concentrations and risk of major adverse cardiovascular events in healthy older women in Australia: a prospective cohort substudy of the ASPREE trial - Islam, R.M.; Bell, R.J.; Handelsman, D.J.; McNeil, J.J.; Nelson, M.R.; Reid, Christopher; Tonkin, A.M.; Wolfe, R.S.; Woods, R.L.; Davis, S.R. (2022)
Background: Blood testosterone concentrations in women decline during the reproductive years and reach a nadir in the seventh decade, after which concentrations increase and are restored to those of reproductive-aged women early in the eighth decade. We aimed to establish the association between the concentration of testosterone in the blood and risk of major adverse cardiovascular events (MACE) and all-cause mortality in healthy older women. Methods: SHOW was a prospective cohort substudy of the longitudinal randomised ASPREE trial. Eligible participants were women aged at least 70 years from Australia with unimpaired cognition, no previous MACE, and a life expectancy of at least 5 years. Participants who were receiving hormonal or steroid therapy were ineligible for inclusion. We measured serum concentrations of sex steroids with liquid chromatography–tandem mass spectrometry and of SHBG with immunoassay. We compared lower concentrations of sex hormones with higher concentrations using four quartiles. Primary endpoints were risk of MACE and all-cause mortality, the associations of which with sex steroid concentrations were assessed using Cox proportional hazards regression that included age, body-mass index, smoking status, alcohol consumption, diabetes, hypertension, dyslipidaemia, impaired renal function, and treatment allocation in the ASPREE trial (aspirin vs placebo). ASPREE is registered with ClinicalTrials.gov, NCT01038583. Findings: Of the 9180 women recruited to the ASPREE trial between March 10, 2010, and Dec 31 2014, 6358 participants provided sufficient biobank samples at baseline and 5535 were included in the final analysis. Median age at entry was 74·0 years (IQR 71·7–77·7). During a median 4·4 years of follow-up (24 553 person-years), 144 (2·6%) women had a first MACE (incidence 5·9 per 1000 person-years). During a median 4·6 years of follow-up (3·8–5·6), 200 women died (7·9 per 1000 person-years). In the fully adjusted models, higher concentrations of testosterone were associated with a lower incidence of MACE (quartile 4 vs quartile 1: hazard ratio 0·57 [95% CI 0·36–0·91]; p=0·02), as were higher concentrations of DHEA (quartile 4 vs quartile 1: 0·61 [0·38–0·97]; p=0·04). For oestrone, a lower risk of MACE was seen for concentrations in quartile 2 only, compared with quartile 1 (0·55 [0·33–0·92]; p=0·02). In fully adjusted models, no association was seen between SHBG and MACE, or between any hormone or SHBG and all-cause mortality. Interpretation: Blood concentrations of testosterone and DHEA above the lowest quartile in older women were associated with a reduced risk of a first-ever MACE. Given that the physiological effects of DHEA are mediated through its steroid metabolites, if the current findings were to be replicated, trials investigating testosterone therapy for the primary prevention of ischaemic cardiovascular disease events in older women would be warranted. Funding: The National Health and Medical Research Council of Australia, US National Institute on Aging, the Victorian Cancer Agency, the Commonwealth Scientific and Industrial Research Organisation, and Monash University.